PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN 3D MATERI TATA SURYA TERKINI BERBASIS ReQOL DALAM MATA PELAJARAN GEOGRAFI DI SMA. - Dea, Anak Agung Istri Sinta; Astutik, Sri; Mujib, Muhammad Asyroful; Kurnianto, Fahmi Arif; Apriyanto, Bejo (Universitas Pendidikan Ganesha, 2024)
Based on the needs analysis questionnaire data, Rambipuji High School students need learning media that is innovative and easy to use. This research prepared a 3D learning animation video on the latest solar system material based on ReQOL. This research aims to examine the validity and responses of students to the development of the latest ReQOL-based animated video learning about the solar system in geography subjects in high school. The type of research used is R&D. The development model used is the ADDIE. The results of this research show validation from material experts, namely 85% and 92.5%, as well as validation results from media experts and geography learning practitioners, namely 98% and 90%. The small and large group student response questionnaires respectively assessed per indicator were 82%-100% and 85%-95.80%. From the results of the validation and student response questionnaire, this video is included in the very good qualifications with very appropriate information, with no need for revision. This research concludes that the latest ReQOL-based 3D learning animation video on solar system material is included in the very good qualifications with very good information, with no need for revision. This video can be used as an innovative learning medium in studying geography in high school with the introduction of new planets.